The robust self-esteem proxy: Impressions of self-esteem inform judgments of personality and social value. Issue 5 (2nd September 2016) - Cameron, Jessica J.; Stinson, Danu Anthony; Hoplock, Lisa; Hole, Christine; Schellenberg, Jodi
Abstract: People use impressions of an evaluative target's self-esteem to infer their possession of socially desirable traits. But will people still use this self - esteem proxy when trait-relevant diagnostic information is available? We test this possibility in two experiments: participants learn that a target person has low or high self-esteem, and then receive diagnostic information about the target's academic success or failure and positive or negative affectivity (Study 1), or watch a video of the target's extraverted or introverted behavior (Study 2). In both experiments, participants' impressions of the target's traits accurately tracked diagnostic information, but impressions also revealed an independent self-esteem proxy effect. Evidently, the self-esteem proxy is robust and influences person perception even in the presence of vivid individuating information.